HUBUNGAN KREATIVITAS MEMBENTUK DAN MERAWAT HAIR PIECE DENGAN HASIL BELAJAR SISWA KELAS X TATA KECANTIKAN RAMBUT SMKN 3 PAYAKUMBUH - Sonita, Betris; Hayatunnufus, Hayatunnufus; Yuliana, Yuliana (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2012)
The purpose of this research is to describe: (1) creativity in form and keeping hair piece, (2) the result of study that is gotten, (3) relationship forming creativity and keeping hair piece with result of study of class X hair beaty SMKN 3 payakumbuh. This research is corelational descriptif research. The population of this research is student of class X 2010-2011 and 2011-2012 SMKN 3 Payakumbuh as many 38 students. The sample is all of population (38 students) with total sampling technique. The result of the research is the first, value average of respondent to creativity variabel of student in forming and keeping hair piece is 34,21 %, it means decrease. Second, result of student’ study in forming and keeping hair piece 29 %, it is above KKM and 71%, under KKM. Third, correlation coefficient between creativity in forming and keeping hair piece with result of student’ study is 0,410, it has enough high relationship.